NU'S INVOLVEMENT IN THE 2024 PRESIDENTIAL ELECTION: A Convergence of Ideological and Pragmatic Motives (State Islamic University (UIN) of Sunan Ampel Surabaya, 2025)
This paper analyzes Nahdlatul Ulama’s (NU) involvement in Indonesia's 2024 Presidential Election, focusing on the convergence of ideological and pragmatic motives. The study examines how different factions within NU align with various presidential candidates, driven by both the desire to protect Aswaja values and the need to maintain relevance in the political sphere. Using qualitative methods by conducting in-depth interviews with several NU circle and political party elites at national and local levels, inside and outside Java, and in the NU-base and non-NU Base regions, this study finds that NU’s political engagement often reflects a mix of ideological commitments to maintain Aswaja doctrine and the non-ideological motives which are the proximity to the party or candidate motive, patronage motive, and economic incentives and access to power motive. The research also highlights the challenges NU faces in maintaining neutrality while navigating the complexities of electoral politics. These diverse interests have ultimately led to polarization within NU and prove that NU is not a monolithic political force. Thus, this paper argues that NU's political participation is an unavoidable aspect of its identity, shaped by ongoing tensions between religious principles and the demands of a changing political landscape.